Montoneros y el PRT-ERP : una propuesta comparativa a partir del análisis de sus posiciones frente al movimiento obrero (1973-1976) - Julieta Pacheco; Guido Lissandrello (Les Cahiers ALHIM)
The historiography of the '70s in Argentina has tended to focus on military deployment of leftist political organizations. Has thus been relegated studying mass fronts. In this article we propose to focus on this last point, stopping at union construction Montoneros and the PRT-ERP for 1973 and 1976. Using internal documents and periodicals, we develop a comparative line for understanding the logic of this construction in the wider political design of each organization.